Accounting, Design, and Website Training for Banyu Biru Hand Fan Craft Hand Fan - Atika Jauharia Hatta; Tri Ciptaningsih; Aruman; Theresia Trisanti; Julianto Agung Saputro; Arif Budiarto (UPT Publikasi Ilmiah UNISBA, 2024)
Abstract. A series of training and mentoring were carried out in community partnership program to improve the ability of the Kipas Banyu Biru Craft SMEs to manage their business. So far, the Kipas Banyu Biru Craft has not kept a record of its financial transactions, so it is difficult to know how much profit is actually earned from this business. In addition, other problems faced by Kipas Banyu Biru Craft are the design of the fan motif which is still simple, as well as marketing that is still traditional and does not use information technology. To overcome this problem, several activities have been carried out. There are providing training and assistance in accounting bookkeeping either manually or using a computer, training and assistance in developing more fan motif designs, and training and assisting internet websites for marketing. The results show that partners are now skilled in bookkeeping and making fan motif designs, and are skilled at using internet websites for marketing their products.